'You started something … then I continued by myself': a qualitative study of physical activity maintenance. Issue 6 (4th August 2017) - Wahlich, Charlotte; Beighton, Carole; Victor, Christina; Normansell, Rebecca; Cook, Derek; Kerry, Sally; Iliffe, Steve; Ussher, Michael; Whincup, Peter; Fox-Rushby, Julia; Limb, Elizabeth; Furness, Cheryl; et al.
Abstract : Background: Most mid-life and older adults are not achieving recommended physical activity (PA) targets and effective interventions are needed to increase and maintain PA long-term for health benefits. The Pedometer And Consultation Evaluation (PACE-UP) trial, a three-armed primary care pedometer-based walking intervention in those aged 45–75 years, demonstrated increased PA levels at 12 months. A three-year follow-up was conducted to evaluate long-term PA maintenance, including a qualitative component. Aim: To examine facilitators and barriers to PA maintenance in mid-life and older adults previously involved in a PA trial. Method: Semi-structured telephone interviews were conducted with 60 PACE-UP participants across all study arms. Interviews were audio-recorded, transcribed verbatim and coded independently by researchers, prior to thematic analysis. Findings: Two-thirds of participants felt since the PACE-UP trial they had an awareness of PA, with the pedometer reported as 'kick-starting' regular activity, and then helped them to maintain regular activity. PA facilitators included: maintaining good health, self-motivation, social support and good weather. Lack of time was the most frequently cited barrier. Other barriers were often the inverse of the facilitators; for example, poor health and bad weather. Participants described the type of 'top-up' intervention they would find beneficial to aid PA maintenance (eg, text messages, online resources and walking groups). Conclusion: A challenge for future PA interventions is to transform barriers into facilitators; for example, educating trial participants about the value of PA for many chronic health conditions to change this from inhibiting to promoting PA. Participants provided ideas for encouraging PA maintenance which could be incorporated into future interventions.